'Tail' autotomy and consequent stinger loss decrease predation success in scorpions. (November 2020) - García-Hernández, Solimary; Machado, Glauco
Abstract : Predation success depends on factors such as hunger, prey size, prey availability and intensity of competition. A neglected factor that may also influence predation success is the proper function of morphological traits related to prey search, capture and manipulation. Injuries that compromise the functionality of these morphological traits may reduce predation success. In many invertebrates, autotomy can compromise predation success because the detached body part may be crucial for hunting. However, empirical evidence linking autotomy and predation success is relatively scarce. We filled this gap using the scorpion Ananteris balzani, which autotomizes the last abdominal segments, known as the 'tail'. This is a unique form of autotomy as 'tail' autotomy implies the loss of the stinger, an organ used for venom inoculation, which is the main form of large prey subjugation. Using a paired experimental design, we found that for both small and large prey, subduing success was higher when individuals were intact than when they were autotomized. After autotomy, subduing success of male scorpions decreased from 90% to 17% for small prey and from 47% to 1% for large prey. Subduing success of female scorpions after autotomy decreased from 98% to 93% for small prey and from 97% to 70% for large prey. Autotomized individuals took longer than intact individuals to subdue both small and large prey, but the effect size was higher for large prey. Considering that the tail does not regenerate, autotomized individuals (especially males) will experience a lifelong reduction in trophic niche breadth because their diet will be mostly composed of small prey. Moreover, autotomized individuals probably move more to enhance the likelihood of finding small prey, which may increase their exposure to predators and consequently the costs related to tail loss. Highlights: Some morphological traits are crucial for prey capture and subjugation. The functionality of these traits is thus crucial for predation success. 'Tail' autotomy in scorpions causes loss of the stinger used for venom inoculation. Stinger loss reduced subduing success of both small and large prey. In conclusion, tail autotomy is costly because it decreases predation success.